Development of highly porous biodegradable gamma-Fe2O3/polyvinyl alcohol nanofiber mats using electrospinning process for biomedical application - Ngadiman, N.; Yusof, N.; Idris, A.; Misran, E.; Kurniawan, Denni (Elsevier, 2017)
The use of electrospinning process in fabricating tissue engineering scaffolds has received great attention in recent years due to its simplicity. The nanofibers produced via electrospinning possessed morphological characteristics similar to extracellular matrix of most tissue components. Porosity plays a vital role in developing tissue engineering scaffolds because it influences the biocompatibility performance of the scaffolds. In this study, maghemite (γ-Fe 2 O 3 ) was mixed with polyvinyl alcohol (PVA) and subsequently electrospun to produce nanofibers. Five factors; nanoparticles content, voltage, flow rate, spinning distance, and rotating speed were varied to produce the electrospun nanofibrous mats with high porosity value. Empirical model was developed using response surface methodology to analyze the effect of these factors to the porosity. The results revealed that the optimum porosity (90.85%) was obtained using 5% w/v nanoparticle content, 35 kV of voltage, 1.1 ml/h volume flow rate of solution, 8 cm spinning distance and 2455 rpm of rotating speed. The empirical model was verified successfully by performing confirmation experiments. The properties of optimum PVA/γ-Fe 2 O 3 nanofiber mats such as fiber diameter, mechanical properties, and contact angle were investigated. In addition, cytocompatibility test, in vitro degradation rate, and MTT assay were also performed. Results revealed that high porosity biodegradable γ-Fe 2 O 3 /polyvinyl alcohol nanofiber mats have low mechanical properties but good degradation rates and cytocompatibility properties. Thus, they are suitable for low load bearing biomedical application or soft tissue engineering scaffold.